Health care reform and the number of doctor visits: An econometric analysis - Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2002)
The paper evaluates the German health care reform of 1997, using the individual number of doctor visits as outcome measure and data from the German Socio- Economic Panel for the years 1995-1999. A number of modified count data models allow to estimate the effect of the reform in different parts of the distribution. The overall effect of the reform was a 10 percent reduction in the number of doctor visits. The effect was much larger in the lower part of the distribution than in the upper part.
Keywords: I11; I18; C25; 330; co-payment; moral hazard; count data; probit-Poisson-log-normal model; Gesundheitsreform; Ärzte; Moral Hazard; Deutschland; Probit-Modell